E-learning module : Biology for form four students "nutrisi" / Zamzurina Saudi - Saudi, Zamzurina (2004)
E-Biology for Form Four Students on "Nutrisi" is one of the educational forms of Elearning system. This system contains about the notes, experiment video presentation, Hangman game and tests. This system will preview the notes, display the experiment video presentation and allow user to answer a test questions after reads the notes and watching the experiment video presentation. User can also measure their performance by playing the Hangman game. In this game user will need to guess a secret word based on the "Nutrisi" topic. This system is developed as an effort to increase the number of e-learning module and number of computer games that can give a lot of benefits for student in their education. It is very useful for students in increasing their effectiveness of learning. Moreover, this system is created to provide a convenient, fun and enjoyable learning environment for Biology subject to make sure that users (students) are convenient and happy with the system. Rather than provides the comprehensive reference, this system should be interactive and effective. This system notes is developed by using a Malay language based on the topic syllabus that teaches in school.